Immigration, integration, and the informal economy in OECD countries - Oussama Ben Atta; Isabelle Chort; Jean Noël Senne (Global Labor Organization (GLO), 2022)
This article assesses the impact of immigrant and asylum seeker in ows on the size of the informal sector in host countries from a macroeconomic perspective. We use two indicators of informality provided by Medina and Schneider (2019) and Elgin and Oztunali (2012) combined with migration data from the OECD Interna- tional Migration Database and data on asylum seeker ows from the UNHCR for the period 1997-2017. We estimate a first-difference model, instrumenting immi- grant and asylum seeker ows by their predicted values derived from the estimation of a pseudo-gravity model. Results suggest that both immigrant and asylum seeker in ows increase the size of the informal sector at destination, but the size of the effect is very small: a one percentage point increase in the stock of immigrants as a share of population leads to an increase of the informal sector as a share of GDP of 0.05-0.06 percentage points. Unsurprisingly, the effect is about four times larger for asylum seeker ows, but remains economically insignificant. We investigate several potential channels, and find that integration policies do matter. We find no impact of imported norms or institutions, but rather that the effect is larger in destination countries with a large informal sector. Finally, we estimate a VAR model and find that the impact of in ows on informality is long-lasting.
Keywords: F22; E26; J46; K37; 330; migration; informal economy; asylum seekers; integration policies; shadow economy